Training program in the lowlands for amateur mountaineers for climbing to the peaks - Ryepko, Olena; Skaliy, Alexander; Tymko, Yevgen; Kozin, Sergiy; Kozina, Zhanneta; Feshchenko, Andrii (H. S. Skovoroda Kharkiv National Pedagogical University, 2023)
Purpose: We develop and experimentally substantiate the use of a method of training amateur mountaineers in conditions of flat terrain to high altitude and ascent to the top. Material and methods: The study involved 12 men (age 20-25 years old) who have 1 year experience in mountaineering. The participants were divided into two groups, control and experimental, 6 people each. The study was conducted from March to August 2021. The intervention program lasted 9 weeks. All participants gave their consent to participate in the experiment. Methods: Physical fitness was measured by the 20 squat test. The resting heart rate was measured while standing. Psychophysiological condition was determined with the "International Reaction Test", the test shows the reaction time to a stimulus. Altitude was chosen as an influence factor on reaction time and HR in different test modes: initial testing (plain), testing at an altitude of 1900 m and at an altitude of 3200 m. Results: The altitude factor had no significant effect on preload reaction time in both control and experimental groups (p>0.05). However, a significant influence of altitude on post-load reaction time was found in both control and experimental groups (p<0,05). HR was significantly influenced by altitude in both control and experimental groups. However, the effect is stronger in the control group than in the experimental group. Conclusions. The method increasing tolerance in hypoxia has a positive effect on the organism recovery after the stress in conditions of natural hypoxia, observed during climbing in the mountains.

Мета: розробити та експериментально обґрунтувати використання авторської методики підготовки альпіністів аматорів в умовах рівнинної місцевості до високогір'я і сходження на вершину. Матеріал і методи: у дослідженні взяли участь 12 чоловіків (вік 20-25 років), які мають досвід занять альпінізмом 1 рік. Учасники були поділені на дві групи: контрольну та експериментальну по 6 осіб. Дослідження проводилося з березня по серпень 2021 року. Програма втручання тривала 9 тижнів. Усі учасники дали свою згоду на участь в експерименті. Методи: Фізичну підготовленість визначали за допомогою тесту "20 присідань". Вимірюється ЧСС у стані спокою стоячи. Психофізіологічний стан визначали за допомогою тесту "Тест на реакцію міжнародний", тестування показує час реакції на подразник. Як фактор впливу на показники час реакції та ЧСС у різних режимах тестування було обрано висоту над рівнем моря: початкове тестування (рівнина), тестування на висоті 1900 м і на висоті 3200 м. Результати: було виявлено, що фактор висоти над рівнем моря впливає не достовірно на час реакції до навантаження і в контрольній, і в експериментальній групах (p>0,05). Однак виявлено достовірний вплив висоти над рівнем моря на час реакції і в контрольній, і в експериментальній групах після навантаження (p<0,05). На показники ЧСС висота над рівнем моря впливає достовірно в обох групах, і в контрольній, і в експериментальній. Однак у контрольній групі цей вплив виражений сильніше порівняно з експериментальною групою. Висновки: методика, що підвищує стійкість у гіпоксії, позитивно впливає на відновлення організму після навантаження в умовах природної гіпоксії, що спостерігається під час підйому в гори.
Keywords: amateur climbers; functional training; hypoxic training; high mountains; альпіністи-аматори; функціональна підготовка; гіпоксичне тренування; високогір'я